2013
DOI: 10.1194/jlr.m037812
|View full text |Cite
|
Sign up to set email alerts
|

CD36 deletion reduces VLDL secretion, modulates liver prostaglandins, and exacerbates hepatic steatosis in ob/ob mice

Abstract: This article is available online at http://www.jlr.org novo FA synthesis or de novo lipogenesis (DNL), decreased FA oxidation, and reduced secretion of VLDLs ( 1, 2 ).CD36 is a class B scavenger receptor that plays an important role in several pathways of FA utilization. The protein is expressed in many cell types, including lingual taste bud cells, enterocytes, adipocytes, myocytes, and immune cells. On taste bud cells, CD36 is important for FA recognition and fat perception ( 3, 4 ). In skeletal muscle, hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 61 publications
7
72
0
Order By: Relevance
“…CD36 signaling has been suggested to play a role in the liberation of AA and subsequent formation of PGs (37). Increased levels of hepatic PGs can negatively affect the hepatic export of VLDL (10,38). We found that HFD-fed CD36Tg mice had significantly reduced hepatic PGE2, PGF2␣, and 6-keto-PGF1 levels compared to their WT controls and the CD36Tg-plus-Dox group (Fig.…”
Section: Creation Of Cd36tg Mice That Overexpress Cd36 In the Liversupporting
confidence: 49%
See 2 more Smart Citations
“…CD36 signaling has been suggested to play a role in the liberation of AA and subsequent formation of PGs (37). Increased levels of hepatic PGs can negatively affect the hepatic export of VLDL (10,38). We found that HFD-fed CD36Tg mice had significantly reduced hepatic PGE2, PGF2␣, and 6-keto-PGF1 levels compared to their WT controls and the CD36Tg-plus-Dox group (Fig.…”
Section: Creation Of Cd36tg Mice That Overexpress Cd36 In the Liversupporting
confidence: 49%
“…The suppression of PGs may have contributed to increased VLDL secretion, because PGs are known to inhibit VLDL secretion from the liver (10,50). The suppressed PG production and increased VLDL secretion in our CD36Tg mice were both consistent with the increased PG levels and decreased VLDL secretion reported for the ob/ob CD36 Ϫ/Ϫ mice (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the role of CD36 in fat perception (22, 70), phospholipid remodeling and eicosanoid production (43), chylomicron production (93), release of intestinal peptides (90) during fat absorption, secretion of hepatic VLDL (66) and adaptation of myocardial rhythm to energy deprivation (73) as highlighted below.…”
Section: Cd36 Signaling Coordinates Fat Metabolismmentioning
confidence: 99%
“…A decrease in VLDL assembly and secretion has been associated with hepatic steatosis [14][15][16]. VLDL particles, which are synthesized in the liver, are responsible for delivering TGs to the different cells of the body.…”
Section: Introductionmentioning
confidence: 99%